Bilanz des gesetzlichen Mindestlohns: Deutliche Lohnerhöhungen, aber auch viele Umgehungen - Toralf Pusch (Wirtschaftsdienst, 2018)
Drei Jahre nach der Einführung des Mindestlohns lässt sich zeigen, dass die Löhne im Niedriglohnsektor wieder gestiegen sind. Nichtsdestotrotz gibt es weiter zahlreiche Umgehungen des Mindestlohns in Deutschland. Eine Schätzung zeigt, dass es dadurch zu jährlichen Lohnausfällen und entgangenen Sozialbeiträgen in Milliardenhöhe kommt. – – Three years after the introduction of the minimum wage in 2015, the assessment of its labour market impact is positive. Contrary to early warnings, there has been no apparent decline in employment in most affected parts of the labour market. The share of the working poor who were eligible for drawing in-work benefits declined by 2.7 percentage points. Nevertheless, there still is a pressing problem of 2.2 million minimum wage violations. Those occur more often in establishments that do not have worker representation and are not covered by collective bargaining. Women and East Germans are also more often affected. Lost wages and social insurance contributions in 2016 were as high as exteuro10 billion.
Keywords: J31; J51; J83; 330